Kepemimpinan Wanita di Indonesia Perspektif Budaya dan Agama - Rahmani Timorita Yulianti (Universitas Islam Indonesia, 2004)
The following article describes the leadership of woman in Indonesia in culture and religion perspective. Entering reformation era now the role of Indonesian woman will change and increase bacause of the opening of opportunity to woman to participate in all aspect of pubic sphere of life, especially in the context of Indonesian leadership. Based on short descripton afore-mentioned, acceding to the author of this articie, it is clear that woman in indonesia can role strategic in public sphere and becomes a member of legislative. So Indonesian woman can play and takes part in an important role toward nation, state and society.